Recognizing Indigenous Peoples’ and Local Communities’ Rights and Agency in the Post-2020 Biodiversity Agenda - Zorondo-Rodriguez, F (Springer Science and Business Media B.V., 2022)
The Convention on Biological Diversity is defining the goals that will frame future global biodiversity policy in a context of rapid biodiversity decline and under pressure to make transformative change. Drawing on the work of Indigenous and non-Indigenous scholars, we argue that transformative change requires the foregrounding of Indigenous peoples’ and local communities’ rights and agency in biodiversity policy. We support this argument with four key points. First, Indigenous peoples and local communities hold knowledge essential for setting realistic and effective biodiversity targets that simultaneously improve local livelihoods. Second, Indigenous peoples’ conceptualizations of nature sustain and manifest CBD’s 2050 vision of “Living in harmony with nature.” Third, Indigenous peoples’ and local communities’ participation in biodiversity policy contributes to the recognition of human and Indigenous peoples’ rights. And fourth, engagement in biodiversity policy is essential for Indigenous peoples and local communities to be able to exercise their recognized rights to territories and resources. © 2021, The Author(s).